Some Long Term Lessons From Minority Language Education in Ontario - Frenette, Normand; Quazi, Saeed (Canadian Journal of Higher Education, 1999)
This paper reports on a comparative and longitudinal study of French-language minority access to higher education in Ontario. The province of Ontario provides homogeneous French-language and bilingual 'mixed' schools at the elementary and secondary levels as well as bilingual institutions at the tertiary level. Since 1990, there has been a homogeneous French language college serving the Eastern region of the province, to which was added two new colleges in 1995. While French- language programs are available throughout the province, it remains that English language programs and institutions are usually more accessible both geographically and regarding the depth and variety of programs. Experience has shown that in this particular minority language setting, it is the offer of minority language educational services that creates the demand, rather than the converse. Thus, the provision of French- medium programs is followed by an increase in minority enrollments and the preference for French-medium programs, even though English- medium programs are more numerous and more convenient. The reduction of French-medium programs is followed by the decline of minority enrollments, even though Francophones are clearly bilingual and in many cases even more at ease in the majority language than in their mother tongue.